2015
DOI: 10.1186/s12862-015-0382-5
|View full text |Cite
|
Sign up to set email alerts
|

Dearth of polymorphism associated with a sustained response to selection for flowering time in maize

Abstract: BackgroundLong term selection experiments bring unique insights on the genetic architecture of quantitative traits and their evolvability. Indeed, they are utilized to (i) monitor changes in allele frequencies and assess the effects of genomic regions involved traits determinism; (ii) evaluate the role of standing variation versus new mutations during adaptation; (iii) investigate the contribution of non allelic interactions. Here we describe genetic and phenotypic evolution of two independent Divergent Select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
63
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(74 citation statements)
references
References 76 publications
(89 reference statements)
11
63
0
Order By: Relevance
“…The dynamics of the response to selection in Saclay divergent selection experiments is consistent with a continuous input of new mutations (Durand, et al 2010). The use of markers also revealed the contribution of complete sweeps from standing genetic variation (Durand, et al 2015). The contribution of both, new mutations and standing variants, to the response to selection to flowering time is consistent with the known complexity of this trait -its high mutation target, i.e.…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations
“…The dynamics of the response to selection in Saclay divergent selection experiments is consistent with a continuous input of new mutations (Durand, et al 2010). The use of markers also revealed the contribution of complete sweeps from standing genetic variation (Durand, et al 2015). The contribution of both, new mutations and standing variants, to the response to selection to flowering time is consistent with the known complexity of this trait -its high mutation target, i.e.…”
Section: Introductionsupporting
confidence: 66%
“…This is particularly intriguing for the two Saclay divergent selection experiments that were conducted independently in two genetic backgrounds (two inbred lines) with limited standing variation (<1.9% residual heterozygosity) and very small population size. In these experiments, by applying divergent selection over 16 generations, we generated considerable phenotypic response with up to three-weeks difference between early and late flowering populations (Durand, et al 2015), a range comparable to what is observed among the maize European Nested Association Mapping panel when evaluated across multiple environments (Lehermeier, et al 2014). The dynamics of the response to selection in Saclay divergent selection experiments is consistent with a continuous input of new mutations (Durand, et al 2010).…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…Explanations for this observation include selective removal of deleterious mutations in native environments or epigenetic differences among the MA lines (Becker et al., 2011). Notably, similar differences between the amount of genetic and phenotypic variation were also found in a selection experiment with maize (Durand et al., 2015). …”
Section: Discussionmentioning
confidence: 99%